Cascade Reactions Catalyzed by Planar Metal–Organic Framework Hybrid Architecture for Combined Cancer Therapy. Issue 42 (28th September 2020) - Mu, Jing; He, Liangcan; Fan, Wenpei; Tang, Wei; Wang, Zhantong; Jiang, Chao; Zhang, Dongyang; Liu, Yijing; Deng, Hongzhang; Zou, Jianhua; Jacobson, Orit; Qu, Junle; et al.
Abstract: Chemical transformation in cellular environment is critical for regulating biological processes and metabolic pathways. Harnessing biocatalytic cascades to produce chemicals of interest has become a research focus to benefit industrial and pharmaceutic areas. Nanoreactors, which can act as artificial cell‐like devices to organize cascade reactions, have been recently proposed for potential therapeutic applications for life‐threatening illnesses. Among various types of nanomaterials, there is a growing interest in 2D metal–organic frameworks (MOFs). By virtue of the ultralarge specific surface area, high porosity, and structural diversity, 2D MOF nanosheets hold great promise for a broad spectrum of biomedical use. Herein, a unique planar MOF‐based hybrid architecture (GMOF‐LA) is introduced by incorporating ultrasmall gold nanoparticles (Au NPs) as nanozyme and l ‐Arginine (l ‐Arg) as nitric oxide (NO) donor. The prepared Au NPs enable oxidation of glucose into hydrogen peroxide, which drives biocatalytic cascades to covert l ‐Arg into NO. Interestingly, the well‐designed nanosheets not only possess excellent catalytical activity for NO generation, resulting in gas therapeutic effect, but also serve as a desired photosensitizer for photodynamic therapy. This study establishes a good example of exploring bioinspired nanoreactors for cooperative anticancer effect, which may pave the path for future "bench‐to‐bedside" design of nanomedicine. Abstract : A planar metal–organic framework (MOF)‐based composite is fabricated by in situ growth of ultrasmall gold nanoparticles and coloading of nitric oxide (NO) donor l ‐Arginine into the MOF structure. Such engineered nanosheets proceed effective cascade reactions toward NO production in addition to combined photodynamic therapy, which offers a promising strategy for the development of advanced nanomedicine.